Petrography and Geochemistry of Gabbroic Rock from the Penjwin Ophiolite, Kurdistan Region, Northeastern Iraq - Sarmad A Ali (Iraqi Geological Journal, 2021)
The gabbroic rocks as a part of Zagros ophiolite are exposed in northeastern Iraq, Penjwin area. These rocks with granular to ophitic textures are widely distributed without metamorphic halos. The main minerals are plagioclase (An90-99), olivine, clinopyroxene (Wo27-47 En 45-64 Fs8-14) and orthopyroxene (Wo2 En78 Fs20) respectively based on the abundances. The major elements show a broad range of compositional variations, with SiO2 (46.2–50.9 wt. %), and low concentrations Na2O (0.15–0.62 wt. %), K2O (0.01–0.03 wt. %) and TiO2 (0.06–0.2) and high concentrations, Al2O3 (6.4–19.75 wt. %), total Fe2O3 (6.29–11.6 wt. %), MgO (9.63–24.5 wt. %), CaO (8.02–18 wt. %) and low alkali contents (Na2O + K2O = 0.16–0.65 wt. %). On Ti-V diagram, all of the gabbroic samples have Ti/V less than 10 and consequently fall in the low Ti- Island arc tholeiitic. Whole rocks chemistry shows a depletion of High field strength elements in comparison with the primitive mantle with an arched upward rare earth elements pattern, characterized by light rare earth elements depletion (La N/Sm N = 0.05–0.8) and enrichment in the High field strength elements. Whole rocks chemistry, mineral paragenesis and chemistry of these rocks are more consistent with tholeiitic magma series. Based on our findings in this research, the primary magma has been produced from the depleted mantle with a high degree of partial melting.